Pronunciation Ability by Using English Song in Indonesian Student of Unswagati Cirebon - Mulatsih, Devi (Universitas Swadaya Gunung Jati, 2015)
Pronunciation is the production of speech sounds for communication. It is the most difficult area of English. This study was conducted under the consideration that pronouncing English words plays an important role. Because of the differences between English and Indonesian pronunciation, many students pronounce English words incorrectly. Data from the Phonetic of English and the rule of how to pronounce English words has been crucial in the development of Phonetics theory throughout its recent past. Explaining the use of English song can increase the pronunciation ability to the students of Unswagati Cirebon in question.